KETERLIBATAN ORANGTUA DALAM PENANGANAN ANAK BERKEBUTUHAN KHUSUS - Khairunisa Rani; rafikayati, ana; Jauhari, Muhammad Nurrohman (Jurnal Abadimas Adi Buana, 2018)
To succeed in early intervention and remember the age of young children, of course the role of parents is important. This is because the parent is the closest child and the person who is always with the child. Parental involvement is very important to realize optimal learning in the golden age of children.It's strengthened by the opinion of Wu and Brown that states that parent participation is one important factor that determines the development of children with special needs. However, in practice many parents still lack understanding of their children. Many parents have difficulty raising their children. Parents do not know what they can do to optimize their child's development. Given the topic of children with special needs is also very limited discussed in general, parents, it is increasingly difficult for parents to get information about how to deal with their children. Based on these problems, the parents of children with special needs need trained to able educate their children properly and children can develop optimally.